Neither Safe Nor Sound? The Perils and Possibilities of Risk - Zedner, Lucia (Canadian journal of criminology and criminal justice, 2006)
The rise of risk as a basis for public policy has profound implications for civil liberties. Where risk prevails over adherence to rules in public policy making, it has the potential to undermine both human rights and basic legal values. The fact that threats to security license derogation from basic rights requires careful attention to the limits to scientific measurement of human risks. Distinguishing between the assessment and the management of risk offers only a partial solution to the danger that political considerations inform and distort risk measurement. Examining how adjacent social scientific disciplines conceive, deploy, and respond to risk and uncertainty reveals a powerful, if problematic, set of analytical resources with which criminology might profitably engage. (English) [ABSTRACT FROM AUTHOR]